GaAs nanowires with oxidation-proof arsenic capping for the growth of an epitaxial shell. Issue 34 (11th August 2016) - Guan, X.; Becdelievre, J.; Benali, A.; Botella, C.; Grenet, G.; Regreny, P.; Chauvin, N.; Blanchard, N. P.; Jaurand, X.; Saint-Girons, G.; Bachelet, R.; Gendry, M.; et al.
Abstract : The reversible As-capping method can avoid the surface oxidation of core nanowires and facilitate the subsequent epitaxial shell growth. Abstract : We propose an arsenic-capping/decapping method, allowing the growth of an epitaxial shell around the GaAs nanowire (NW) core which is exposed to an ambient atmosphere, and without the introduction of impurities. Self-catalyzed GaAs NW arrays were firstly grown on Si(111) substrates by solid-source molecular beam epitaxy. Aiming for protecting the active surface of the GaAs NW core, the arsenic-capping/decapping method has been applied. To validate the effect of this method, different core/shell NWs have been fabricated. Analyses highlight the benefit of the As capping–decapping method for further epitaxial shell growth: an epitaxial shell with a smooth surface is achieved in the case of As-capped–decapped GaAs NWs, comparable to the in situ grown GaAs/AlGaAs NWs. This As capping method opens a way for the epitaxial growth of heterogeneous material shells such as functional oxides using different reactors.